Imaging cAMP nanodomains in the heart - Chao, Y; Surdo, N; Pantano, S; Zaccolo, M (Portland Press, 2019)
3′-5′-cyclic adenosine monophosphate (cAMP) is a ubiquitous second messenger that modulates multiple cellular functions. It is now well established that cAMP can mediate a plethora of functional effects via a complex system of local regulatory mechanisms that result in compartmentalized signalling. The use of fluorescent probes to monitor cAMP in intact, living cells have been instrumental in furthering our appreciation of this ancestral and ubiquitous pathway and unexpected details of the nano-architecture of the cAMP signalling network are starting to emerge. Recent evidence shows that sympathetic control of cardiac contraction and relaxation is achieved via generation of multiple, distinct pools of cAMP that lead to differential phosphorylation of target proteins localized only tens of nanometres apart. The specific local control at these nanodomains is enabled by a distinct signalosome where effectors, targets, and regulators of the cAMP signal are clustered. In this review, we focus on recent advances using targeted fluorescent reporters for cAMP and how they have contributed to our current understanding of nanodomain cAMP signalling in the heart. We briefly discuss how this information can be exploited to design novel therapies and we highlight some of the questions that remain unanswered.